2018
DOI: 10.1038/s41586-018-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatal swine acute diarrhoea syndrome caused by an HKU2-related coronavirus of bat origin

Abstract: Cross-species transmission of viruses from wildlife animal reservoirs poses a marked threat to human and animal health . Bats have been recognized as one of the most important reservoirs for emerging viruses and the transmission of a coronavirus that originated in bats to humans via intermediate hosts was responsible for the high-impact emerging zoonosis, severe acute respiratory syndrome (SARS) . Here we provide virological, epidemiological, evolutionary and experimental evidence that a novel HKU2-related bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
733
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 632 publications
(802 citation statements)
references
References 25 publications
15
733
0
15
Order By: Relevance
“…Generally, bats are considered to be important reservoirs of novel emerging infectious diseases. Circovirus host jumps may be a risk for both the pig industry and public health, similar to the recently reported bat‐origin coronavirus detected in pigs 39, 40…”
Section: Discussionsupporting
confidence: 77%
“…Generally, bats are considered to be important reservoirs of novel emerging infectious diseases. Circovirus host jumps may be a risk for both the pig industry and public health, similar to the recently reported bat‐origin coronavirus detected in pigs 39, 40…”
Section: Discussionsupporting
confidence: 77%
“…Our results showed that the first SADS‐CoV positive sample was collected in August 2016 from the farm LS with a history of diarrhoea, as well as from other two farms TP and ZW, which indicates that SADS‐CoV has emerged in pigs in China at least since August 2016. And this time point is 5 months earlier than the first discovered time reported by our previous study (Zhou et al., ). As the same time, clinical signs of SADS‐CoV during the retrospective investigation included sever and acute vomiting and diarrhoea, leading to death in piglets that were less than 5 days of age with a mortality rate of around 50%.…”
Section: Discussionmentioning
confidence: 39%
“…Swine acute diarrhoea syndrome coronavirus (SADS‐CoV) is a newly discovered coronavirus which is an enveloped, positive and single‐stranded sense RNA virus with a genome size of approximately 27 kb (Gong et al., ; Pan et al., ; Zhou et al., ). SADS‐CoV belongs to the family Coronaviridae which contains four genera, Alphacoronavirus, Betacoronavirus, Gammacoronavirus, and Deltacoronavirus (Woo, Huang, Lau, & Yuen, ; Woo et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies will need to validate these platforms in differing geographic contexts and with influenza subtypes. Conceivably, they hold utility for rapidly identifying and controlling other priority transboundary animal disease pathogens, including viral etiologies of porcine reproductive and respiratory syndrome (PRRS), classical swine fever (CSF), African swine fever (ASF), and emerging coronaviruses with a livestock transmission interface . The August 2018 notification by China to international authorities concerning the detection of African swine fever virus in domestic swine across multiple provinces presents an opportunity to trial such PoC diagnostic platforms at scale in a region that represents a substantial portion of the global swine production industry.…”
Section: Scaling To Other Disease Surveillance and Control Applicatiomentioning
confidence: 99%